2020
DOI: 10.1136/bmjopen-2020-036998
|View full text |Cite
|
Sign up to set email alerts
|

Clinically SUspected ScaPhoid fracturE: treatment with supportive bandage or CasT? ‘Study protocol of a multicenter randomized controlled trial’ (SUSPECT study)

Abstract: IntroductionSome scaphoid fractures become visible on radiographs weeks after a trauma which makes normal radiographs directly after trauma unreliable. Untreated scaphoid fractures can lead to scaphoid non-union progressing to osteoarthritis. Therefore, the general treatment for patients with a clinically suspected scaphoid fracture and normal initial radiographs is immobilisation with below-elbow cast for 2 weeks. However, most of these patients are treated unnecessarily because eventually less than 10% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Over-treatment of suspected scaphoid injuries is an ongoing challenge [1] . Cohen et al [26] stated that less than 10% of patients placed on follow up pathways are ever diagnosed with a fracture. In our study, 20% of those referred for CBCT were confirmed positive for bony injury, although the number of scaphoid fractures were small.…”
Section: Discussionmentioning
confidence: 99%
“…Over-treatment of suspected scaphoid injuries is an ongoing challenge [1] . Cohen et al [26] stated that less than 10% of patients placed on follow up pathways are ever diagnosed with a fracture. In our study, 20% of those referred for CBCT were confirmed positive for bony injury, although the number of scaphoid fractures were small.…”
Section: Discussionmentioning
confidence: 99%
“…Usual management of patients with suspected scaphoid fractures involves immobilisation in a cast or splint and further imaging to either exclude or confirm a definite fracture [6].…”
Section: Introductionmentioning
confidence: 99%